Раскопки укрепленного поселения Дикий Сад в 2009 г. - Горбенко, К.В.; Козленко, Р.А. (Археологічні дослідження в Україні, 2010)
The main results of the research of Dykyi Sad, a fortified settlement of Bilozerska culture in Mykolayiv, are presented. They covered the western section of a ditch with the remains of a basement of the second bridge and rooms 9 (manufacturing complex) and 11.